2005
DOI: 10.1111/j.1460-9568.2005.03897.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel transcription factor Satb2 interacts with matrix attachment region DNA elements in a tissue‐specific manner and demonstrates cell‐type‐dependent expression in the developing mouse CNS

Abstract: Satb1 is a first cell-type-specific transcription factor of a novel type that functions as a regulator of the transcription of large chromatin domains. We identified a close homologue of Satb1, Satb2, in a cDNA subtraction screening in a search for genes controlling neural differentiation. Satb2 showed 61% amino-acid homology to Satb1. Satb2 and Satb1 expression was detected in different cell subpopulations of developing mouse CNS in a mutually exclusive manner. In the electrophoretic mobility shift assay we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
234
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(250 citation statements)
references
References 23 publications
14
234
0
2
Order By: Relevance
“…Cortical neurons can be identified by immunostaining with antibodies recognizing neuronal markers such as Brn2, Satb2, Ctip2, Foxp2, and Tbr2 (Bulfone et al, 1999;McEvilly et al, 2002;Ferland et al, 2003;Arlotta et al, 2005;Britanova et al, 2005). We detected expression of all of these markers in Mkk7 flox/flox Nestin-Cre cortex (Fig.…”
Section: Impaired Axon Formationmentioning
confidence: 99%
“…Cortical neurons can be identified by immunostaining with antibodies recognizing neuronal markers such as Brn2, Satb2, Ctip2, Foxp2, and Tbr2 (Bulfone et al, 1999;McEvilly et al, 2002;Ferland et al, 2003;Arlotta et al, 2005;Britanova et al, 2005). We detected expression of all of these markers in Mkk7 flox/flox Nestin-Cre cortex (Fig.…”
Section: Impaired Axon Formationmentioning
confidence: 99%
“…SATB2 belongs to the family of special AT-rich sequence-binding proteins, members of which are present in the nuclear matrix and can bind to AT-rich sequences, activating the transcription of particular genes (Britanova et al 2005). In vivo studies have shown that Satb2 physically interacts with and enhances the activity of Runx2 and Atf4 (Dobreva et al 2006, Conner & Hornick 2013.…”
Section: Mirnas and Osteoblast Differentiationmentioning
confidence: 99%
“…Basal progenitors differ from apical progenitors in terms of gene expression: they do not express astroglial markers, nor the transcription factors Pax6 and Hes (Cappello et al 2006;Englund et al 2005), while they can be positively identified by the expression of Tbr2 (Englund et al 2005), Cux1 and 2 (Conti et al 2005), VGlut2 (Schuurmans et al 2004), Satb2 (Britanova et al 2005) and the non-coding RNA Svet1 (Tarabykin et al 2001).…”
Section: Basal Progenitorsmentioning
confidence: 99%